2022
DOI: 10.1002/jsfa.11896
|View full text |Cite
|
Sign up to set email alerts
|

Maize ear growth is stimulated at the fourth day after pollination by cell wall remodeling and changes in lipid and hormone signaling

Abstract: BACKGROUND: Stimulating maize ear development is an effective way of improving yield. However, limited information is available regarding the regulation of sink strength change from weak to strong at the same position of maize plants. Here, a novel method for stimulating development combined with physiological assays and proteomics was applied to explore the regulation of ear strengthened development.RESULTS: By blocking pollination of the upper ear of maize hybrid Suyu 41, the adjacent lower ear was dramatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Our previous study indicated that IAA, ABA, and cytokinin are mainly enriched at the 4 DAP in treatments that stimulate sink activities of early kernels (Du et al, 2022). We also found that IAA, cytokinin, and ABA metabolism were enriched mainly at the gene level (Figure S4) and few genes were enriched at the protein level (Figure S5).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Our previous study indicated that IAA, ABA, and cytokinin are mainly enriched at the 4 DAP in treatments that stimulate sink activities of early kernels (Du et al, 2022). We also found that IAA, cytokinin, and ABA metabolism were enriched mainly at the gene level (Figure S4) and few genes were enriched at the protein level (Figure S5).…”
Section: Resultsmentioning
confidence: 97%
“…At the time of husk emergence, two different pollination systems, herein named synchronouspollination (SP) and pollination-blocking and hand-pollination (PBH) were used. In a previous study, treatments-designated SP and PBH were referred to as NP and HP, respectively (Du et al, 2022). In the SP systems, the upper and lower ears were bagged before silk emergence, and when most of the silks emerged on both ears, they were F I G U R E 1 Overview of the ear pollination experimental design and sample collection.…”
Section: Plant Materials and Pollination Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the characterization of plant cell wall proteins remains challenging and requires a combination of various analytical approaches, there have been rapid advances in cell wall protein research combined with proteomics approaches ( Komatsu and Yanagawa, 2013 ; Adelaide et al., 2018 ). To gain information about protein changes in cell walls, many types of stress-associated cell wall proteins have been identified in crops, and these researches have shown that cell wall proteins play an important role in stress signal transduction, cell defense and rescue, cell wall modification, etc ( Wolf, 2017 ; Du et al., 2022 ; Wolf, 2022 ). The top leaflets showed less stress signs by salinity have an increased expression of cell wall-related genes in tomato ( Hoffmann et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%